Patrimonio alimentario y desarrollo del turismo gastronómico del cantón Guano, Provincia de Chimborazo. - Silva Vargas, Carlos Fabricio (2023)
The respect for the food heritage takes its real importance based on the research that is generated to rediscover the food wonders that the environment has and have the potential to become important tourism resources for their use, which is why the research aims to determine the influence of food heritage in the development of gastronomic tourism in the Guano canton, with the methodology whose type of research was documentary, descriptive and correlational, non-experimental and cross-sectional research design. With the application of the evaluation instruments, it was detected that although the null hypotheses were validated, it is necessary to recognize the great importance of gastronomy at a cultural level, as seen by restaurant owners and tourist, who considered that the design of a gastronomic route is fundamental, according to the data obtained through the cross SWOT strategic tool, ratifying that the favorite motivation of local and national tourist is its culinary offer.